Synovial Macrophage and Fibroblast Heterogeneity in Joint Homeostasis and Inflammation - Knab, Katharina; Chambers, David; Krönke, Gerhard (Frontiers in Medicine, 2022)
The synovial tissue is an immunologically challenging environment where, under homeostatic conditions, highly specialized subsets of immune-regulatory macrophages and fibroblasts constantly prevent synovial inflammation in response to cartilage- and synovial fluid-derived danger signals that accumulate in response to mechanical stress. During inflammatory joint diseases, this immune-regulatory environment becomes perturbed and activated synovial fibroblasts and infiltrating immune cells start to contribute to synovial inflammation and joint destruction. This review summarizes our current understanding of the phenotypic and molecular characteristics of resident synovial macrophages and fibroblasts and highlights their crosstalk during joint homeostasis and joint inflammation, which is increasingly appreciated as vital to understand the molecular basis of prevalent inflammatory joint diseases such as rheumatoid arthritis.